Baicalin promotes embryo adhesion and implantation by upregulating fucosyltransferase IV (FUT4) via Wnt/beta‐catenin signaling pathway. Issue 11 (17th April 2015) - Zhang, Yu-Mei; Zhang, Yuan-Yuan; Bulbul, Ahmmed; Shan, Xiu; Wang, Xiao-Qi; Yan, Qiu
Abstract : Glycosylation plays a significant role in determining the receptivity of the uterine endometrium to embryo. Fucosyltransferase IV (FUT4) is expressed stage‐specifically in the uterine endometrium of mammalians, and considered as a marker of the endometrial receptivity. Baicalin, a monomer of flavonoids, is known to have functions in improving reproduction. However, the mechanism by which baicalin regulates the expression of FUT4 in embryo‐endometrium adhesion remains unclear. Our results showed that baicalin significantly increased FUT4 mRNA and protein expression levels both in human endometrial cells and mouse endometrial tissue, and consistently elevated embryo adhesion rate during implantation in vitro and embryonic implantation competence in pregnant mouse. This study suggests that baicalin facilitates endometrial reproduction via elevating FUT4 expression through Wnt/β‐catenin signaling pathway. Abstract : Baicalin elevates FUT4 expression in human and mouse endometrium. Baicalin enhances the adhesion of embryonic JAR cells to endometrial RL95‐2 cells. Baicalin facilitates embryo implantation in mouse model. Baicalin increases the endometrial receptivity by upregulating FUT4 mediated via Wnt/β‐catenin signaling pathway.